Socioeconomic Inequalities in Child Malnutrition in the Developing World - Wagstaff, Adam; Watanabe, Naoko (World Bank, Washington, DC, 2014)
Among the conclusions the authors reach about malnutrition rates, among different economic groups: 1) inequalities in malnutrition almost disfavor the poor; 2) it's not just that the poor have higher rates of malnutrition. The rate of malnutrition declines continuously with rising living standards; 3) the tendency of poorer children to have higher rates of stunting, and underweight, is not due to chance, or sampling variability. Inequalities in stunting, and underweight, as measured by the concentration index, are statistically significant in almost countries; 4) inequalities in underweight tend to be larger than inequalities in stunting, which tend to be larger than inequalities in wasting; 5) in most cases, whatever the malnutrition indicator, differences in inequality between countries are not statistically significant; 6) even if attention is restricted to the cross-country differences in inequality that are statistically significant, interesting conclusions emerge, Egypt, and Vietnam have the most equal distributions of malnutrition, and Nicaragua, Peru, and, to a lesser extent, Morocco, have highly unequal distributions; 7) some countries (such as Egypt and Romania) do well in terms of both the average (the prevalence of malnutrition) and the distribution (equality). Others do badly on both counts. Peru, for example, has a higher average level of stunting than Egypt, and higher poor-non-poor inequality. But many countries do well on one count, and badly on the other. Brazil, for example, has a far lower (less than 20 percent) stunting rate overall, than Bangladesh (more than 50 percent), but has four times as much inequality (as measured by the concentration index); 8) use of an achievement index that captures both the average level, and the inequality of malnutrition, leads to some interesting rank reversals in the country league table. With stunting, for example, focusing on the achievement index moves Egypt (a low-inequality country) from sixth position to fourth, higher than Brazil and Russia (two countries with high inequality).